Peer Teaching in High-Fidelity Simulation Participant Experiences and Reflections - Lawrence, Kay (Nurse Educ, 2018)
Peer teaching provides students with opportunities to experience the educator role and increase self-confidence and problem-solving skills. To address the shortage of meaningful leadership experiences for senior baccalaureate nursing students, faculty implemented an alternative leadership experience involving senior students taking on the role of peer teachers in the high-fidelity simulation (HFS) laboratory. We conducted focus groups to assess peer teachers and learners’ experiences and used thematic analysis to examine and interpret the data. Findings included the intersection of learning, HFS, clinical experience, and teaching; the benefits of practicing teaching in a safe environment; how empathy enhanced understanding of the continuum of expertise; and power differentials experienced by peer teachers and learners.